Podcasting as a needs-analysis tool in higher education - Tapia López, Alicia; Carrero Márquez, Oliver (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Drawing on a qualitative-descriptive analysis of quality surveys, validated by ANECA (2017-2022), this study describes the process undertaken to improve the Data and Source Libraries course included in the second-year university curriculum of a Spanish university by applying teaching methodologies centered on “learning by doing”. This pedagogic initiative encouraged students to participate in the entire process of creating a podcast. The findings of this study, which spanned four academic years, suggest that the students believe podcasting is a tool that connects them to their professional surroundings and motivates them to develop their creativity and critical reasoning.